The Analysis of Potential Growth for Indonesia’s Micro Small Medium Business Owners - Christian Haposan Pangaribuan; Okta Prihatma Bayu Putra; Lidhiah Lesthary; Glory Aguzman; Desman Hidayat (International Journal of Business Studies, 2018)
This study examines the relation between potential growth in the context of micro, small, medium enterprises by evaluating several factors, i.e. lack of marketing ability, inadequate business training, technological backwardness, poor quality of products, lack of innovation, unfavorable legal and regulatory framework, insuficient capital, and shortage of skilled labor. The data collected is from 196 self-employed enterprises in Jakarta, Indonesia. Results indicate that unfavorable legal and regulatory framework is the most affecting factor to slow down the growth of small businesses as well as a hindrance to its exports opportunities abroad. The further investigation of demographic factors shows how the differences canadd to ourunderstanding in the potential growth of smallbusinesses.